2017
DOI: 10.13057/biodiv/d180417
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: The potential of various indigenous Trichoderma spp. to suppress Plasmodiophora brassicae the pathogen of clubroot disease on cabbage

Abstract: Suada IK. 2017. Short Communication: The potential of various indigenous Trichoderma spp. to suppress Plasmodiophora brassicae, the pathogen of clubroot disease on cabbage. Biodiversitas 18: 1424-1429. On the island of Bali, cabbage (Brassica oleracea L.) is a vegetable that has high economic value especially for farmers who cultivate it as a cash crop. However, the clubroot disease caused by the microbial pathogen Plasmodiophora brassicae decreases its productivity. Much effort has been expended in attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…During the experiment, it was observed that as the storage time of banana leaves increased, physical characteristics such as weight and color of the upper surface varied. Regarding leaf length and width, these values coincide with those reported by Suada [84], who obtained the following results: leaf length 257.70 ± 27.66 cm, and leaf width 70.23 ± 5.83 cm. On the other hand, Tan et al [7] determined that the percentage of juice extracted and filtered was 33% (v/p), and Chai et al [50] estimated a percentage of 36% (v/p); however, in this work, a maximum average value of 13% (v/p) was calculated.…”
Section: Determination Of Factors Affecting the Concentration Of Redu...supporting
confidence: 90%
“…During the experiment, it was observed that as the storage time of banana leaves increased, physical characteristics such as weight and color of the upper surface varied. Regarding leaf length and width, these values coincide with those reported by Suada [84], who obtained the following results: leaf length 257.70 ± 27.66 cm, and leaf width 70.23 ± 5.83 cm. On the other hand, Tan et al [7] determined that the percentage of juice extracted and filtered was 33% (v/p), and Chai et al [50] estimated a percentage of 36% (v/p); however, in this work, a maximum average value of 13% (v/p) was calculated.…”
Section: Determination Of Factors Affecting the Concentration Of Redu...supporting
confidence: 90%
“…The genus Trichoderma is a well known soil-borne saprophytic fungus that is widely distributed in all soil types (Mera-jul et al 2012;Kalaivani et al 2014;Wu et al 2014). It is a good biocontrol agent as it suppressing the development of plant pathogens by producing antifungal enzymes such as chitinase and 1,3 gluconase (Harman 2006;Suada 2017). It also produces phytohormones such as auxins, which are required by plants (Haneefat et al 2012) to increase their resistance to drought stress (Yu et al 2014).…”
Section: Introductionmentioning
confidence: 99%